Incorporating usability requirements in a test/model-driven web engineering approach - Robles Luna, Esteban
The success of Web applications is constrained by two key features: fast evolution and usability. Cur- rent Web engineering approaches follow a unified development style which tends to be unsuitable for applications that need to evolve fast. Moreover, according to the quality standard ISO 9126-1, us- ability is a key factor to obtain quality systems. In this paper, we show how to address usability re- quirements in a test-driven and model-based Web engineering approach. More specifically, we focus on usability requirements with functional implications, which do not only concern the visual appear- ance, but also the architecture design. Usability requirements are contemplated from the very begin- ning of each cycle, by creating a set of meaningful tests that drive the development of the application and ensure that no functionality related to usability is altered unintentionally through development cycles. Dealing with those usability requirements in the very early steps of the software development process avoids future hard changes in the system architecture to support them. The approach is illus- trated with an example in the context of the OOWS suite.